Implementasi IoT Dan Algoritma Fuzzy Untuk Monitoring Kualitas Air Pdam Menggunakan Aplikasi Blynk - Samsudin, Ceceng Muhamad; Rahmawati, Diah; Sofyan, Asep Abdul (JURNAL ILMIAH FAKULTAS TEKNIK, 2025)
Clean water quality is vital to public health. At Perumdam TKR Tangerang, the monitoring system is not fully IoT-based, risking water degradation. This study designs a water quality monitoring tool using NodeMCU ESP8266, DS18B20 temperature sensor, pH sensor, and TDS sensor. Data is transmitted to Blynk and Telegram for remote monitoring. Fuzzy Logic is applied to classify water as “Normal” or “Not Normal.” The prototype method includes user needs analysis, system design, and testing. Results show the tool can accurately detect water parameters and send automatic alerts when values exceed limits. This system offers an effective and affordable solution for water quality monitoring